DAMPAK TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH TERHADAP KESEHATAN MASYARAKAT DI DESA BATUNADUA KECAMATAN PADANGSIDIMPUAN BATUNADUA KOTA PADANGSIDIMPUAN PROVINSI SUMATERA UTARA - Dawet Alraniri Harahap; Paus Iskarni (JURNAL BUANA, 2022)
Placement of waste management locations in TPA Batubola which is not far from settlements, rivers and also in hills that are higher than rivers and settlements. Condition of TPA Batubola Garbage is an object that is no longer needed by humans, has limitations and does not meet the criteria for location placement The landfill actually causes damage to the surrounding environment. This study aims to analyze the impact of the Batubola landfill on public health in Batunadua Village, Padangsidimpuan District, Batunadua, Padangsidimpuan City. Data collection was carried out by distributing questionnaires to the community, with a total of 165 respondents, the Batunadua area was divided into two, namely Batunadua Jae and Batunadua Julu. 24.6% while Batunadua Julu whose knowledge level is Good 23.0%, Adequate 53.3% and Less 23.6%. The results of the level of knowledge that the Batunadua community is classified as moderately knowledgeable. Then the health problems in Batunadua consist of Diarrhea 19, 3%, Itching 36.9%, Hepatitis A 2.42%. DHF 17.5%, Cough 20% and shortness of breath 63%. This is presumably due to damaged environmental conditions caused by TPA Batubola, due to TPA Batubola will cause environmental pollution that has an impact on public health in Batunadua.